Mothers' Perceptions of Quality of Family-Centered Care and Environmental Stressors in Neonatal Intensive Care Units: Predictors of and Relationships with Psycho-emotional Outcomes and Postpartum Attachment. - Kim, Ah Rim; Tak, Young Ran; Shin, Yong Soon; Yun, E. Hwa; Park, Hyun-Kyung; Lee, Hyun Ju (Maternal & Child Health Journal, 2020)
Objectives: Maternal attachment to promote role development in mothers of preterm infants is critical for babies' optimal growth and development. However, few models specify how neonatal intensive care units (NICUs) and their environments work to foster postpartum attachment (PPA) after preterm birth. We investigated relationships of quality of family-centered care and NICU environmental stressors with maternal PPA, to determine whether these are mediated by mothers' psycho-emotional response and whether pathways to PPA are moderated by developmental immaturity (gestation, birthweight). Methods: A cross-sectional study using structural equation modeling was conducted on 294 mothers of premature infants with experience in NICUs in over 49 tertiary hospitals in 12 cities or provinces of South Korea. Data were collected using Korean versions of instruments including the Quality of Family-centered Care, Parental Stressor Scale: NICU, and Maternal Postpartum Attachment Scale. Results: Maternal self-representation was a key predictor of PPA (β =.68), accounting for 42.2% of variance. Multi-group analysis indicated that NICU environmental stressor sensitivity (β =.26) and maternal self-representation (β =.67) were predictive of PPA in mothers of moderately preterm and low birthweight (32–36 weeks' gestation, 1500–2499 g birthweight) infants. Quality of family-centered developmental care (β =.11) and NICU environmental stressor sensitivity (β = −.16) had significant indirect effects on PPA through psycho-emotional responses. Conclusions for Practice: Healthcare professionals should be aware of the importance of family-centered interventions focusing on psychosocial support and family participation in baby care, based on their environmental role in promoting PPA.